Symphonic Volume in the Symphony-Requiem by Bohdana Frolyak “Pravednaya Dushe” - Volovchuk, Yuliia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. The article is relevant as it studies the works of Bogdana Frolyak, who is a popular contemporary Ukrainian composer. Her music attracts the attention of performers and researchers and reflects the current trends of contemporary art such as musical language, new forms of choral sound, synthesis of genres. The Requiem Symphony “Righteous Ssoul” (lyrics by T. Shevchenko) is an example of a complex multidimensional nature genre renewal. Therefore, lack of research devoted to this work outlines a scientific novelty of this article. The objective of the study is to identify the features of symphony in the symphonyrequiem “Righteous Soul” by B. Frolyak. The research methodology is based on the interpretation analysis method proposed by V. Moskalenko. The concept of A. Adamyan is used to study symphonic principles. Results. Analysing the requiem symphony “Righteous Soul”, it was determined that the leading role is devoted to chorus, which serves as a main mean of expression. The choir is regarded as a symbol of collegiality and stands in as an active participant in the formation of musical thought and sounds through almost the entire opus (except for two vocal episodes). T. Shevchenko’s poetic lines are entrusted to mixed chorus and embody a main idea of the work. Choral fragments serve various functions starting from the creation of a harmonic background to being a main storyteller. At the same time, B. Frolyak’s composition realizes symphonic principles, which display themselves at different levels of organization of musical material. Symphonic patterns are expressed in timbre-textured and thematic connections, cross-cutting development, national instrumentation color and intonation transformations of themes. The composer’s principle of artistic thinking reveals parallels with the symphonic concept developed by A. Adamyan. Conclusion. A special genre multidimensionality is expressed in the symphony-requiem “Pravednaya Dushe”. B. Frolyak enriches the semantic layer of the work due to the features of the requiem. Composer takes an advantage of the cathedral’s choral sonority rich possibilities and uses the symphonic intonation and dramatic basis. At the intonation level, she unites all these features with the help of solospiv (solosining) — a musical symbol of Ukrainian nation. Finally, unique synthesis of supersubstantial spiritual and philosophic ideas with universal (symphony, requiem) and national characteristic (solospiv) genres makes B. Frolyak’s work one of the most original in the series of Ukrainian choral symphonies.